2022
DOI: 10.1155/2022/9709648
|View full text |Cite
|
Sign up to set email alerts
|

Improved CNN Method for Crop Pest Identification Based on Transfer Learning

Abstract: Timely treatment and elimination of diseases and pests can effectively improve the yield and quality of crops, but the current identification methods are difficult to achieve efficient and accurate research and analysis of diseases and pests. To solve this problem, this study proposes a crop pest identification method based on a multilayer network model. First, the method provides a reliable sample dataset for the recognition model through image data enhancement and other operations; the corresponding pest ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Several studies have demonstrated the effectiveness of AI‐based insect identification in the field. For example, one study found that a CNN achieved an accuracy rate of 97% in identifying wild bee species (Buschbacher, Buschbacher, et al., 2020) and various pest species with similar precision (Johari et al., 2023; Liu et al., 2022). Another study used an AI algorithm to classify ladybird beetles with an accuracy rate of 92% (Venegas et al., 2021).…”
Section: Ai Methods For Species Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated the effectiveness of AI‐based insect identification in the field. For example, one study found that a CNN achieved an accuracy rate of 97% in identifying wild bee species (Buschbacher, Buschbacher, et al., 2020) and various pest species with similar precision (Johari et al., 2023; Liu et al., 2022). Another study used an AI algorithm to classify ladybird beetles with an accuracy rate of 92% (Venegas et al., 2021).…”
Section: Ai Methods For Species Identificationmentioning
confidence: 99%
“…In several studies, AI systems have been used to identify and track the spread of insect pests that can cause significant damage to crops and ecosystems (Aigner et al., 2016; Caselli & Petacchi, 2021; Chithambarathanu & Jeyakumar, 2023; Deka et al., 2022; He et al., 2019; Li et al., 2021; Liu et al., 2022; Xia et al., 2018; Zhao, Liu, et al., 2022; Zhao, Zhou, et al., 2022). For example, researchers have used AI to analyse satellite imagery to identify areas where pest outbreaks are occurring, providing an early warning and allowing for proactive management strategies (Gómez‐Camperos et al., 2022; Meraj et al., 2022; Pourghasemi, 2021).…”
Section: Fields That Benefit From Ai Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bao et al [26] developed a new technique e-ISSN : 0976-5166 p-ISSN : 2231-3850 for diagnosing wheat leaf diseases and severity based on elliptical-maximum margin criteria metric learning; it has an identification accuracy of 94.16 percent. Based on Inception-ResNet-v2 and VGG-16, Liu et al [29] developed a system for identifying and categorising crop pests. On the IDADP dataset, it earned an average accuracy score of 97.71%.…”
Section: Literature Surveymentioning
confidence: 99%
“…The former includes YOLO [1], SSD [2], and so on; the detection results are available immediately after testing, so it has a faster detection speed but is less capable of detecting small target spodoptera frugiperda. Faster-CNN [3], Mask R-CNN [4], and others are examples of the latter, which have slightly higher recognition accuracy [5], but slightly lower detection speed and cannot meet real-time performance requirements. Both methods have advantages, but neither can simultaneously meet the accuracy and real-time requirements of spodoptera frugiperda detection [6,7].…”
Section: Introductionmentioning
confidence: 99%